2013
DOI: 10.1186/1749-7922-8-17
|View full text |Cite
|
Sign up to set email alerts
|

World society of emergency surgery study group initiative on Timing of Acute Care Surgery classification (TACS)

Abstract: Timing of surgical intervention is critical for outcomes of patients diagnosed with surgical emergencies. Facing the challenge of multiple patients requiring emergency surgery, or of limited resource availability, the acute care surgeon must triage patients according to their disease process and physiological state. Emergency operations from all surgical disciplines should be scheduled by an agreed time frame that is based on accumulated data of outcomes related to time elapsed from diagnosis to surgery. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 10 publications
1
71
0
13
Order By: Relevance
“…One of similar the features of blunt trauma, gunshot wounds, stab wounds, GIS bleeding, mesenteric ischemia, GIS perforations, is that they are in the emergency surgery class that requires intervention for immediate or several hours. Mortality is high if early intervention is not performed in these emergencies [19]. In our study, we concluded that these surgeries, which are in the Immediate and emergency class requiring intervention within several hours, are not affected by the COVID 19 pandemic.…”
Section: Resultsmentioning
confidence: 60%
“…One of similar the features of blunt trauma, gunshot wounds, stab wounds, GIS bleeding, mesenteric ischemia, GIS perforations, is that they are in the emergency surgery class that requires intervention for immediate or several hours. Mortality is high if early intervention is not performed in these emergencies [19]. In our study, we concluded that these surgeries, which are in the Immediate and emergency class requiring intervention within several hours, are not affected by the COVID 19 pandemic.…”
Section: Resultsmentioning
confidence: 60%
“…157,183,[195][196][197][198] The question of timely and effective intervention A challenge in surgery is, among other things, the time frame -there is an interrelation of postponing acute surgery and the increased risk of developing complications. 199 In contrast, we would need time before surgery to intervene and allow time for recovery from organ dysfunctions and related improvements of postoperative complications.…”
Section: Follow-upmentioning
confidence: 99%
“…In 2013, the World Society for Emergency Surgery Study Group (WSES) recommended the use of a color system to classify emergency surgeries to reduce the loss of information and to allow the establishment of standardized language among the teams. Timing of Acute Care Surgery (TACS) was based on a survey of a panel of specialists about the ideal time for more frequent emergency surgeries 6 .…”
Section: Introductionmentioning
confidence: 99%